THE ROLE OF MAJELIS TA’LIM IN SHAPING ADOLESCENT CHARACTER - Sugiyanto Sugiyanto; Putri Yulista Damayanti (El-Fatih: Jurnal Dakwah dan Penyuluhan Islam, 2025)
Adolescence is a transitional stage from childhood to adulthood, marked by physical, cognitive, and social changes. This study aims to examine the role of Majelis Ta’lim Hidayatuttaqwa in shaping the character of adolescents in Kp. Lio No. 28, Jatinegara Subdistrict, Cakung District, as well as to identify the supporting and inhibiting factors in the process. The research employs a qualitative method with a descriptive approach. The researcher conducted fieldwork to collect data and obtain the necessary information for the study. Data collection techniques included observation, interviews, and documentation. The findings reveal that Majelis Ta’lim Hidayatuttaqwa plays a significant role in shaping adolescent character through: (1) the inculcation of Islamic religious knowledge and (2) the development of adolescent character. These aspects are essential for adolescents; therefore, Majelis Ta’lim Hidayatuttaqwa strives to meet these needs in order to have a tangible impact and provide meaningful benefits for the youth